Economic cycles in peru. Three perspectives - Erquizio Espinal, Oscar Afredo (2022)
The evolution of the world economy and national economies is marked by di- fferent types of cycles: long-term Kondratieff cycles, financial cycles and crises, classical economic cycles. They are related and somehow nested. Here through an analysis of the contributions in this regard and in honor of the work of Bruno Seminario, who addressed these issues for the Peruvian case. The downswings of the five global Kondratieff cycles are revealed to contain thirteen of the fourteen global recessions identified from the late nineteenth century to now. The eight classic economic cycles of Peru and their respective recessions for the period 1950-2020 are also identified, which are also clearly nested in the downward pha- ses of the Kondratieff cycles revealed by Seminario and which are characterized as the recessions of the global cycles by declines in gross domestic product per person. Additionally, it is found that the recessions of the classic economic cycles of Peru are characterized by significant values due to their magnitude of their res- pective sectoral, regional and sectoral-regional diffusion indices. What opens the door to study from this perspective the regional manifestations of these classic cycles in Peru.